Joint X̄ and R Charts with Variable Sample Sizes and Sampling Intervals - Costa, Antonio F. B. [UNESP] (My University, 1999)
Recent studies have shown that the X̄ chart with variable sampling intervals (VSI) and/or with variable sample sizes (VSS) detects process shifts faster than the traditional X̄ chart. This article extends these studies for processes that are monitored by both the X̄ and R charts. A Markov chain model is used to determine the properties of the joint X and R charts with variable sample sizes and sampling intervals (VSSI). The VSSI scheme improves the joint X̄ and R control chart performance in terms of the speed with which shifts in the process mean and/or variance are detected.
Keywords: Adjusted Average Time to Signal; Markov Chains; Statistical Process Control; Variable Sample Size; Variable Sampling Intervals